Corticosteroids commonly prescribed in pediatric patients undergoing full-mouth rehabilitation under general anesthesia: A retrospective study - A Divya Dharshini; Lavanya Govindaraju (Wolters Kluwer Medknow Publications, 2022)
Dental treatment under GA is a compelling method for giving therapeutically important consideration to those youngsters who might be intellectually juvenile, exceptionally restless, medicinally split the difference, or unfit to get treatment in a customary office setting. While the traditional work on concerning corticosteroids is likely innocuous and perhaps gainful with lower prophylactic dosages and the nature of oral admission was additionally unaffected. The study aimed to investigate commonly prescribed corticosteroids in children undergoing full-mouth dental management under general anesthesia. A single-centered retrospective study among pediatric patients treated under general anesthesia of the age group of 0-13 years. The sample size is 124. Data were collected and tabulated. Data were statistically analyzed using the SPSS software version 23. Chi-square test and Pearson correlation were done using the software and P < 0.05 was considered statistically significant. The results show that 79.67% commonly prescribed dexamethasone, whereas 20.33% use hydrocortisone, providing the age groups between 0 and 3 has higher prescribing of corticosteroids. From this study, it is concluded that since the P value was more than 0.05, there is no significant statistical difference that has been analyzed. Dexamethasone is the commonly prescribed corticosteroid in children undergoing full-mouth rehabilitation under GA, followed by hydrocortisone.